Satisfaction and challenges of beneficiaries of the Yolanda Permanent Housing Program in a component city of the Philippines - Villanueva-Golez, Alore; Alo, Evangeline B.; Bual, Joel M. (Technium Social Sciences Journal, 2024)
The Yolanda Permanent Housing Program (YPHP) in the Philippines was designed to resettle the poor families affected by typhoon Yolanda/Haiyan in 2013. There were 1,992 units granted to the component city but as of July of 2022, only 1,067 units were awarded. Hence, this study determined the satisfaction of the beneficiaries of YPHP and identified the challenges they encountered when they resettled at the site. Likewise, it investigated the difference in their satisfaction relative to length of stay and family size. Using the descriptive-comparative approach, this study was responded by 283 beneficiaries determined using simple random sampling. It utilized a validated and reliability-tested researcher-made questionnaire and checklist. Generally, their satisfaction was rated high. However, the areas that need continuous improvement are community development and relocation process which were rated low. Meanwhile, there were challenges identified in terms of application and documentation processing, relocation and transfer, occupancy, and livability. Also, there was no difference in their satisfaction as to length of stay and family size. However, in terms of length of stay, there was a difference in safety and suitability of location. Given the findings, continuous improvement by the implementers is necessary.